Susceptibility to auditory feedback manipulations and individual variability - Muge Ozker; Peter Hagoort (PLoS ONE, 2025)
Monitoring auditory feedback from hearing one’s own voice is important for fluent and precise speech production as it enables the detection and correction of speech errors. This influence is evident when auditory feedback is manipulated, such as through delayed auditory feedback (DAF), which affects speech fluency by slowing speech rate, or pitch-perturbed auditory feedback (PAF), which affects vocalization leading to changes in voice pitch. Previous studies have tested both DAF and PAF in clinical populations and showed that susceptibility to these manipulations varied largely across individuals with different disorders. However, it remains unclear whether this variability stems from different task manipulations, as no single study has systematically tested both types of feedback manipulations within the same population. DAF and PAF affect different aspects of speech likely engaging distinct neural mechanisms. It remains uncertain whether individuals highly susceptible to one type of manipulation will also be susceptible to the other. To address this, we examined neurotypical individuals instead of clinical populations, allowing us to better control background variability. In addition to task manipulations, we were also interested in why individuals within a population vary in their susceptibility under each task manipulation. One possible explanation for individual differences in susceptibility is that some individuals rely more on auditory feedback, making them more sensitive to disruptions, while others depend more on alternative sensory modalities, rendering them less affected. Visual feedback, such as seeing one’s own mouth movements, has been shown to improve speech production in clinical populations with impairments. We aimed to test whether providing visual feedback as an alternative sensory modality could similarly reduce the effects of altered auditory feedback on speech in neurotypical individuals, particularly among those who may rely more on non-auditory sensory feedback. We recorded voice samples from 40 neurotypical participants during DAF and PAF tasks. In the DAF task, participants repeated sentences while experiencing delayed feedback, which significantly reduced their speech rate. In the PAF task, participants phonated a sustained vowel sound and experienced unexpected pitch perturbations in their auditory feedback. In most trials, they adjusted their voice pitch in the opposite direction to compensate for the perturbation. We assessed susceptibility to DAF and PAF by examining speech rate and peak amplitude of the compensatory response, respectively. Participants highly susceptible to DAF experienced notable speech rate reductions, while those highly susceptible to PAF exhibited larger pitch adjustments. Susceptibility varied widely among participants, with no consistent overlap between those sensitive to DAF and those sensitive to PAF, supporting distinct processing mechanisms for these different manipulations. Additionally, to examine the effect of visual feedback on speech production, we focused on the DAF task, as it involves visible mouth movements during sentence repetition. In some trials, participants received visual feedback by watching themselves speak through a webcam. Contrary to expectations, this immediate visual feedback did not alleviate but rather strengthened the disruptive effects of DAF, further reducing speech rate.